Molecular Characterization and Expression of unc-13d in the Sex Reversal of Monopterus albus - Zitong Lian; Fang Meng; Xueping Xia; Junchao Fang; Haifeng Tian; Qiaomu Hu (Animals)
Monopterus albus is a protogynous hermaphroditic fish that changes from female to male, but the underlying sex change mechanism remains as-yet unknown. In this study, we firstly cloned and characterized the sequence and protein structure of unc-13d of M. albus. We found that the genomic structure of unc-13d was different from other species. Expression was detected in the developing gonad by applying qRT-PCR and in situ hybridization. We found that the expression of unc-13d in the ovotestis was higher than in the ovary and testes. A strong signal of unc-13d was detected in oocytes and granulosa cells in the ovary and spermatogonia and primary spermatocytes in the testes. We found that the promoter methylation of unc-13d was negatively correlated with gene expression in developing gonads, especially at site 114. A dual-luciferase assay was designed and revealed that dmrt1 regulates promoter activity opposite to foxl2. In summary, during sex reversal, DNA methylation affects the binding of the transcription factor dmrt1 and foxl2 in the promoter region through methylation and demethylation interactions to regulate the expression of unc-13d during gonadal development.